Analisis Pengaruh Environment, Social, Governance (ESG) Disclosure Terhadap Kinerja Keuangan Perusahaan - Nugroho, Naufal Adi; Hersugondo Hersugondo (LPPM Universitas Sains dan Teknologi Komputer, 2022)
This case study discusses the effect of Environmental Disclosure (EVN), Social Disclosure (CSR), Governance Disclosure (CG) and Environmental, Social, Governance (ESG) disclosure on company performance, using control variables including asset turnover and asset growth. The variables that will be used in this study are the dependent variable (Return on Assets), independent variables (ESG disclosure, EVN disclosure, CSR disclosure, and Corporate Govenance Disclosure), and control variables (asset turnover and asset growth). The population in this sample will use manufacturing companies listed on the Indonesia Stock Exchange with a range of 2016-2020. Samples will be taken by purposive sampling method. Based on purposive sampling, it was found that there were 25 manufacturing companies listed on the IDX (2016-2020) that had complete data. The data analysis method used in this research is multiple regression analysis. In addition, this research also uses statistical techniques to test the hypothesys proposed in this study, namely panel data using SPSS. This study found that overall ESG Disclosure has a significant positive effect on company performance and CSR Disclosure has a significant negative effect on company performance.